Pleomorphic adenoma of the palate: A case report - Tom, Jibin Jose; Puthalath, Ushass; VP, Sreejith; Nair, Aparna S; MC, Vidhya Vijayan; M, Amrutha Krishnan (Journal of Orofacial Research, 2024)
Pleomorphic adenoma is a benign tumor of the salivary glands with complex morphology, possessing both epithelial and myoepithelial elements arranged in a variety of patterns. This type of tumor most commonly arises in the parotid or submandibular glands. Infrequently, it may arise from the minor salivary glands and present as an intraoral mass over the palate or lip. Here we present a case report on a hard palate swelling; FNAC revealed a benign salivary gland lesion, further radiographic & histopathological examination confirmed the diagnosis pleomorphic adenoma of the palate. The aim of this article is to present a case of palatal Pleomorphic adenoma, which was treated successfully by surgical excision.